Comparative Analysis of The Industrial Estate Development in Riau - Jahrizal, Jahrizal; Topani, Heru (International Journal of Economic, Business & Applications, 2017)
Industrial estate in Riau has been developed on four (4) districts and cities. It turned out that only two districts become a national strategic program. This study analizes potential resources industrial estatein Riau; What advantages industrial estatedistricts of the city in the Riau; and the potential for industrial relations in the municipal district in Riau on development of industrial estates.The method used is quantitative research with the Resources Based Theory which discusses the variables of human resources, natural resources, infrastructure, technology, and finance the development of industrial estates. The population of this region is 4 (four) regions.The study results showed that the growing industrial estate are Siak and Dumai. Those regions are more developed because of their variable institution / organization, availability of land, and Tenans.